2018
DOI: 10.1111/nmo.13523
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxoplasma gondii infection alters the number of neurons and the proportion of enteric glial cells in the duodenum in Wistar rats

Abstract: Background Toxoplasma gondii infection can occur through the ingestion of raw meat that contains tissue cysts or food that contains oocysts. Through the ingestion of oocysts, the parasite crosses the intestinal barrier, where the enteric nervous system is located. The objective was to investigate the kinetics of neuronal and glial responses during acute T. gondii infection. Methods We used 45 Wistar rats that were divided into a control group and infected groups that were evaluated at 6, 12, 24, 48, 72 hours, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…It is important to point out that attenuated GI transit time and diarrhea were correlated with a decreased nNOS enteric inhibitory subpopulations in diabetic animals (Ferreira et al, 2018). Previous studies demonstrated that hyperglycemia‐related oxidative stress and inflammation are primary inducers of enteric nervous system dysfunction, resulting in marked changes in intestinal motility and intestinal secretion activity (Chandrasekharan et al, 2011; Trevizan et al, 2019; Voukali et al, 2011). Herein, we identified some changes in intestinal morphology and evidence of enteric nervous system remodeling in GK rats; however, the underlying mechanisms responsible for these alterations are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to point out that attenuated GI transit time and diarrhea were correlated with a decreased nNOS enteric inhibitory subpopulations in diabetic animals (Ferreira et al, 2018). Previous studies demonstrated that hyperglycemia‐related oxidative stress and inflammation are primary inducers of enteric nervous system dysfunction, resulting in marked changes in intestinal motility and intestinal secretion activity (Chandrasekharan et al, 2011; Trevizan et al, 2019; Voukali et al, 2011). Herein, we identified some changes in intestinal morphology and evidence of enteric nervous system remodeling in GK rats; however, the underlying mechanisms responsible for these alterations are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The myenteric plexus was obtained by removing the submucosal tissue and mucous layer. The submucosal plexus was obtained by removing the mucosal and muscular layer (Trevizan et al, 2019). A total of 10 animals (five per group) were used for this set of experiments.…”
Section: Methodsmentioning
confidence: 99%
“…However, the neuroplastic response to inflammation enables intestinal homeostasis (Mawe et al, 2009). Hypertrophy of neuron bodies in the myenteric plexus at 90 days of infection suggests an increase in their metabolic activity; this acts as a mechanism of adaptation to adverse conditions suffered by these cells (Araujo, 2015;Trevizan et al, 2019). Such alterations can interfere with intestinal motility and consequently lead to an increase in muscle layers, as this plexus is responsible for the coordinating movements of intestinal relaxation and contraction (Nezami and Srinivasan, 2010;Machado et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, enteric glial cells and their products participate in intestinal homeostasis, especially in neuronal survival. Thus, the reduction of these cells has already been suggested to be associated with infectious [115,116] and noninfectious intestinal diseases [117][118][119], which are characterized by 4 Journal of Immunology Research neurodegeneration, like in CD. Evidence shows a glial cell and neuron network owing to the production of NTs such as NGF, NT-3/4/5, and glial cell line-derived neurotrophic factor (GDNF).…”
Section: Peripherinmentioning
confidence: 99%